La gestión del capital humano en la empresa Danper Trujillo S.A.C., periodo 2017-2022 - Llajaruna Quiñones, Maritza Margarita (2023)
This report entitled: "The management of human capital in the company Danper Trujillo S.A.C., period 2017-2022", details the functions performed as Human Capital Management Assistant in this organisation during the last four years, with the objective of serving as a reference framework to determine the functions performed in this position, the experience lived, provide information on the main problems that afflict the area; and finally make a proposal for improvement in the organisation as well as in the curriculum of this professional school. Thus, the following chapters were considered: Chapter I, presentation of the Danper Company and its location in the national and local context, including the organisation chart of the institution and the description of the functions developed according to its MOF. I also identified the problems that exist in the exercise of my functions; and finally, I indicated the general and specific objectives of this report. Chapter II, the theoretical basis was made around the problems identified within the organisation, developing a critical study of the tasks performed. Chapter III, the main strategies for solving the problems identified were established. Chapter IV, a critical judgement was made of the university training received in the School of Management. In this sense, it was concluded that the main problems identified were the delay in the delivery of forms, deviation in the attendance register and non-compliance in the delivery of information, which were treated as alternative solutions.